Japan's natural resources and their relation to Japan's economic future - Ackerman, Edward A. (University of Chicago Press, 1953)
A reference of Japan's Resources including food supply, energy sources, and raw materials, and makes suggestions for management. Illustrated with many excellent photographs, maps and graphs.